From defeat to victory : the Eastern Front, summer 1944 - Dick, Charles (Modern war studies. Decisive and indecisive military operations, 2016)
"The second of two volumes that look at military operations--the connecting link between specific battlefields and broader strategic goals--against the German army during a pivotal year in World War II. Focusing here on those operations designed and executed on the Eastern Front by Stalin and his military commanders, Dick examines how and why a resurrected Red Army was by 1944 decisively rolling back a Wehrmacht now in full retreat. As in the first volume, he places his analysis within the context of the combatants' military thought and leadership, battlefield experiences, and logistical realities."--Provided by publisher.